Assessment of von Willebrand Factor/ADAMTS13 Ratio and Vitamin K Levels as Predictor Markers for Severity of COVID-19 Patients - Mohsin, Haneen Saeed; Ali, Hanaa Addai; Al-Tu'ma, Fadhil Jawad (Journal of Contemporary Medical Sciences, 2021)
Objectives: To investigate the levels of each of von Willebrand Factor, ADAMTS-13, and vitamin K in sera of Iraqi patients infected with Covid-19 and study the association between them to explore the mechanism roles of micro thrombosis in Covid-19 progression. Methods: In this case-control study, a total of (60) COVID-19 patients (min-max) aged (35-65years) who presented within 7-12 days of displaying COVID-19 symptoms were recruited. (30) apparently healthy persons of the same ages and gender were included in this study as a control group. patients were divided into three groups: mild patients group (n=33), sever patients group (n = 15), and deceased group (n = 12). In this study, the levels of vWF, ADAMTS-13, and vitamin K were measured through enzyme-linked immunosorbent assays (ELISA) in sera from healthy volunteers as a control group, and patients with moderate COVID-19, patients with severe COVID-19, and patients who had deceased from COVID-19. Anthropometric, biochemical data were analyzed. Results: The levels of vWF, ADAMTS-13, and vitamin K were did differ significantly among groups. However, the level of vWF was significantly higher in moderate COVID-19 and severe cases of COVID-19 groups compared to control indicating it to be an independent predictor in the coronavirus disease. The levels of vitamin K were significantly lower in the patients group than the control group especially in severe case of the COVID-19 group. In contrast, the level of vWF in deceased COVID-19 patients was significantly higher compared to severe cases. The vWF /ADAMTS13 ratio was higher at presentation in COVID-19 patients who died (26.14 vs 12.34; P < .0001). Linear regression analysis for vWF levels revealed significant negative correlations with ADAMTS-13, and vit. K ,and positive correlations with d-dimer and ferritin levels. However ADAMTS-13 demonstrated significant positive correlations with vit.K levels in patients group. Conclusion: The correlations of vWF-ADAMTS-l3 and vitamin K levels in Covid-19 patients could help better define the pathophysiology, clarify the pathogenesis, improve prediction of clinical prognosis, and better guide thromboprophylaxis and treatment Covid-19 patients, which could be uses as hall mark of severe Covid-19 and provide a rational for combined therapeutic approaches for medical staff. A ratio of vWF/ADAMTS-13 prompt higher in the ratio in thrombolysed patients was associated with increased mortality and morbidity.